(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The paper offers a philosophical reframing of natural resource use. It aims to develop a normative-ontological framework for decision-making that balances intergenerational responsibility, ecosystem integrity, and fair governance of commons. Methods include hermeneutic analysis, normative ethics, conceptual modeling, and comparative inquiry. Results synthesize Jonas’s imperative of responsibility, Ostrom’s design principles for commons, Heidegger’s account of the essence of technology, and Leopold’s land ethic to articulate robust criteria for sustainable use. The discussion qualifies the scope of the “tragedy of the commons,” contrasts market-utilitarian approaches with strong sustainability, and foregrounds risk ethics under uncertainty. A five-step, practice-oriented decision protocol is proposed for resource projects.